2001
DOI: 10.1523/jneurosci.21-11-04059.2001
|View full text |Cite
|
Sign up to set email alerts
|

Large Involuntary Forces Consistent with Plateau-Like Behavior of Human Motoneurons

Abstract: When electrical stimulation is applied over human muscle, the evoked force is generally considered to be of peripheral origin. However, in relaxed humans, stimulation (1 msec pulses, 100 Hz) over the muscles that plantarflex the ankle produced more than five times more force than could be accounted for by peripheral properties. This additional force was superimposed on the direct response to motor axon stimulation, produced up to 40% of the force generated during a maximal voluntary contraction, and was abolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
236
3
17

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(286 citation statements)
references
References 44 publications
30
236
3
17
Order By: Relevance
“…The patterns of stimulation were similar to those used in previous studies (1,8,9,41). In the first pattern, there was a 3-s "100-Hz burst" in a 7-s stimulation train.…”
Section: Methodssupporting
confidence: 52%
See 3 more Smart Citations
“…The patterns of stimulation were similar to those used in previous studies (1,8,9,41). In the first pattern, there was a 3-s "100-Hz burst" in a 7-s stimulation train.…”
Section: Methodssupporting
confidence: 52%
“…In fact, the development of extra torques was similar for the biceps and FPL despite their different Ia monosynaptic connectivity. Furthermore, the enhanced torques had similar profiles to those in lower limb muscles (8,9,33) and wrist flexors (1). The extra torque development in FPL shows that strong Ia monosynaptic projections are not required for the development of enhanced force of central origin (see Ref.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Studies have also been undertaken on humans, with an emphasis on recording the discharge of single motor units (e.g., Kiehn and Eken, 1997). In selected instances, the data have suggested that plateau potentials are involved in the observed firing patterns (Eken and Kiehn, 1989;Kiehn and Eken, 1997;Gorassini et al, 1999Gorassini et al, , 2000Collins et al, 2001Collins et al, , 2002aWalton et al, 2002). To study the mechanisms (i.e., PICs and their modulation) underlying repetitive firing during behavior, however, it is necessary to use intracellular recording techniques.…”
Section: State-dependence Of Motoneuron Properties: Modulation Duringmentioning
confidence: 99%